New specific primer matK and rbcL region for DNA barcode pitcher plant Nepenthes spathulata - MUHAMMAD NANDA UTAMA; NITA ETIKAWATI; SUGIYARTO SUGIYARTO; ARI SUSILOWATI (Society for Indonesian Biodiversity, 2024)
Abstract. Utama MN, Etikawati N, Sugiyarto, Susilowati A. 2024. New specific primer matK and rbcL region for DNA barcode pitcher plant Nepenthes spathulata. Biodiversitas 25: 2515-2523. The matK and rbcL genes were proposed as the preferred plant barcoding loci by The Consortium for the Barcode of Life (CBOL). DNA barcoding efficiently identifies samples at the species level using short standard DNA sequences. The identification disclosure needs is an important basis given the confusion in systematics in Nepenthes spathulata. Therefore, this study aims to design matK and rbcL region-specific primers for DNA barcoding pitcher plants. The primary design uses Primer3Plus with a blueprint from the GenBank KDQ007081.1 for matK and MH346374.1 for rbcL. Following testing primary candidates with Oligo Analyzer and Primer-BLAST, the primers MkNs1, and RbNs4 were selected as the optimal criteria based on the values of ?G and primer specificity. Optimization of annealing temperature with PCR gradient shows that the temperature range 52-57°C produces a good band for both regions and corresponds to the matK and rbcL region with product sizes of 800-900 bp from seven samples, which could be observed from the gel electrophoresis. Sequence similarity using blast-N, the matK sequence has similarity to the N. spathulata matK gene of 99.64% and 99.63% for the rbcL gene of N. ventricosa x N. alata. This MkNs1 and RbNs4 primer can be used to discover the identity of N. spathulata and the Nepenthes genus.